Neuroendocrine breast carcinoma - Laura Pratas Guerra; Joana Simões; Diogo Carvalho Sá; José Polónia; António Araújo (University of São Paulo, 2024)
Neuroendocrine breast cancer (NEBC) is a rare and heterogeneous entity. It most commonly presents a luminal phenotype and a worse prognosis. When diagnosed in an advanced stage, metastasis from another neuroendocrine tumor should be excluded.This case features a premenopausal woman with an oligometastatic breast large cell neuroendocrine carcinoma, estrogen receptor (ER) positive, and human epidermal growth factor receptor 2 (HER2) negative. Since the patient was very symptomatic at the presentation of the disease, chemotherapy was started. Complete radiological response of the metastatic disease was achieved, and the patient was then submitted to radical breast surgery and bilateral oophorectomy. She subsequently underwent radiation therapy. Since then and to date, she has been under endocrine therapy (ET) and a CDK4/6 inhibitor (CDK4/6i), with no evidence of malignant disease. Evidence to guide the choice of treatment for these tumors is currently scarce. In cases with oligometastatic disease, radical treatment should be considered. Given that this entity is rare, its reporting should be encouraged.